Kajian Sosial Ekonomi Pada Masyarakat Nelayan Tradisional di Desa Ponelo, Kecamatan Ponelo Kepulauan, Kabupaten Gorontalo Utara - Patamani, Izhar; Harold, Rudy; Ibrahim, Ridwan (Dynamics of Rural Society Journal, 2023)
This study aims to explain the phenomenon of the low level of economic well-being of traditional fishing families who live in Ponelo Village, Ponelo Kepulauan District, and North Gorontalo Regency. This study uses a qualitative method. The results of this study indicate that the level of economic welfare of traditional fishermen in Ponelo Village is still low. This condition can be seen in the data, where most of the people of Ponelo Village are in prosperous family categories 1 and 2. One of the causes of poverty among traditional fishermen is that the income of these families still depends on their work as fishermen with very low productivity because The means of production are still very simple, namely nets, trawls, and fishing rods. To increase people's income, the government seeks to provide assistance with equipment, housing, food needs, education, and housing.